Students’ Learning Styles in Using U-Dictionary Application on Learning English - Said, Erpin; Sahib, Naina Zena Ali; Jamal, Adira Nuryanindi; Saputra, Dian (JULIET: Journal of English Language and Literature, 2024)
This study aims to explore the students’ learning style in using U-Dictionary on learning class, specifically at SMA Muhammadiyah Al-Amin. The qualitative method was applied in this study. In collecting the data, the writer used questionnaire and interview. Nine students who were chosen for this study based on their English teacher's assigned scores for each class are the participants. The questionnaire and interview are used in this research to collect the data. These instruments were adopted from Nihaya (2011) “In this study use questionnaire and interview was given to students to determine the learning styles of students in 11th grade at SMA Muhammadiyah Al-Amin Sorong City”. The result shows that most of students have 3 types of learning style, there are 6 (46%) students is visual learner as dominant learning style, the second is 4 (31%) students are kinesthetic, and the last is 3 (23%) students are auditory. It means that students’ learning style in using U-Dictionary most likely is visual learner